Internal and External Factors Affecting Sales Decline of Traditional Bakery Products: A Case Study in East Java - Naila Dio Tito Brata Ibrahim; Lilis Sulandari; Ila Huda Puspita Dewi; Nufimbar Susy Anindita (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study investigates the internal and external factors that contributed to the declining sales of pandan-flavored steamed brownies at PT Citra Kendedes Cake and Bakery, a traditional food-based MSME in Malang, East Java. Using a qualitative single-case study design, the research drew on in-depth semi-structured interviews, direct field observations, and internal sales and production records from 2017 to 2024. The findings show that the decline was shaped by interconnected internal and external pressures. Internally, the product suffered from limited innovation, inconsistent quality control, weak knowledge standardization, and inadequate digital marketing adoption. Externally, the business faced stronger competition from modern bakeries, changing consumer preferences toward novelty and visual appeal, and intensifying market pressure in digitally mediated food retail. Together, these factors explain a sustained sales decrease of approximately 35% over seven years. The study highlights that traditional food-based MSMEs cannot rely on product heritage alone; they must continuously adapt their human resources, product development processes, pricing logic, packaging, and branding strategies to remain relevant. These findings contribute practical insight into how culturally rooted bakery products can be repositioned more effectively in a competitive contemporary market. Keywords: consumer preference shift; internal business factors; local SME bakery; market competition; traditional food products